Chemotherapy of porcine hereditary lymphosarcoma - Brownlie, Serena Elizabeth (The University of Edinburgh, 1980)
A hereditary form of lymphosarcoma in Large White pigs, associated with an autosomal recessive gene, is diagnosed usually before 3 months of age and is fatal by 15 months. The suitability of this condition for testing anticancer chemotherapeutic agents has been investigated using four agents representing each of the four major modes of action. Prednisolone, adriamycin (doxorubicin), cyclophosphamide and cytarabine as single agents were administered to normal pigs to determine appropriate dose levels and then to lymphosarcoma cases, and the results compared with previously reported effects in man and other species. Prednisolone produced a reduction in numbers of circulating lymphocytes and in size of lymph nodes, which was striking in the lymphosarcomatous pigs, an increase in serum albumin and decrease in serum globulins and involution of the thymus with "overshoot" on recovery. The lymphosarcoma cases showed improvements in appetite and vigour and in neutrophil, thrombocyte and red cell counts. Adriamycin was cumulatively toxic at high dose levels, producing bone marrow depression, involving all types of white blood cells, red cells and thrombocytes, gastro-intestinal damage, stunting of growth, alopecia, stomatitis, sclerosis of blood vessels and possibly cardiotoxicity . Lymphosarcoma cases did not survive a dose level of 2mg/kg. One of these died of liver failure. A dose-level of 1mg/kg produced a general improvement in fitness, body condition and weight gain with temporary suppression of the tumour after each dose. Cyclophosphamide produced few effects, other than a consistent reversible, neutropenia during the 1st week after dosing, even at high dose-levels. Alopecia and haemorrhagic cystitis were not seen. Depression of skin delayed hypersensitivity response and thymus involution were unexpected results. Lymphosarcoma cases showed evidence of temporary suppression of the tumour after each dose. Normal pigs given cytarabine showed slight weight loss and progressive bone marrow depression. Antitumour effect was disappointing, only one lymphosarcomatous animal showing evidence of response, despite the fact that levels of deoxycytidine kinase, which activates cytarabine, were shown to be four times higher in lymphoid tissue from the lymphosarcoma cases compared with the normal pigs. Normal pigs given cytarabine showed slight weight loss and progressive bone marrow depression. Antitumour effect was disappointing, only one lymphosarcomatous animal showing evidence of response, despite the fact that levels of deoxycytidine kinase, which activates cytarabine, were shown to be four times higher in lymphoid tissue from the lymphosarcoma cases compared with the normal pigs.
The chemotherapy of porcine hereditary lymphosarcoma